Patterned electroconductive networks in Ag-polyamide 6 composites by laser ablation - Oliveira, Filipa M. (2021)
A simple, fast, and cost-effective method to fabricate conductive paths on insulating Ag-containing polyamide 6 (PA6) composites by laser beam treatment is presented in this study. First, Ag-hybrid microparticles (Ag-MP) with a total metal load of up to 19 wt% are synthesized based on a reactive encapsulation strategy utilizing activated anionic polymerization of-caprolactam in solution, in the presence of Ag nanoparticles. Then, the Ag-MP are compression molded into plates (Ag-PL) on which a scanning laser treatment is applied to create conductive paths in their selected parts. A comparison between structural, morphological, and thermal properties of the Ag-MP and the molded Ag-PL composites is performed. The electric conductive properties of the Ag-loaded hybrid materials are investigated before and after laser ablation, and it is concluded that the laser treatment results in selected paths with widths in the range of 500μm with conductivity values in the range of 1.12 to 8.90 S m−1while the untreated Ag-PA6 surface remains isolating with conductivity values of 1.27×10−08Sm−1.These results prove that applying laser ablation with controlled parameters on initially insulating Ag-PL composites can efficiently produce conductive line patterns in composite plates.